Literature Review Transformasi Digital Dalam Administrasi Kesehatan Masyarakat: Inovasi Sistemik Untuk Meningkatkan Efektivitas Layanan Publik Di Tahun 2025 - Nurcholisah Fitra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to analyze the systemic impact of digital transformation on public health administration in Indonesia through a systematic literature review approach. The research was conducted by synthesizing 24 peer-reviewed articles published between 2019 and 2025, using the PRISMA method for structured selection and data synthesis. The findings reveal four dominant thematic focuses: adoption of health information systems, human resource readiness, system interoperability, and digital governance policies. While digitalization has improved administrative efficiency and data quality, challenges such as system fragmentation and limited digital literacy persist. The study concludes that successful digital transformation in health administration depends not only on technological innovation but also on institutional integration, policy coherence, and capacity development. The implications suggest the need for coordinated digital policies and capacity-building programs to ensure inclusive and sustainable digital health governance.